2022
DOI: 10.1186/s12913-022-07999-z
|View full text |Cite
|
Sign up to set email alerts
|

Exploring clinician perceptions of a care pathway for the management of shoulder pain: a qualitative study

Abstract: Background Clinical care pathways may be useful tools to improve the quality of healthcare by facilitating the translation of evidence into practice. Our study is situated within a larger project, whereby end-users co-developed a care pathway for the management of shoulder pain. In this study, we explored end-user perceptions of the usefulness and practicality of implementing a care pathway to manage shoulder pain. We also solicited feedback for the pathway’s improvement. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…It has been suggested that clinical care pathways could serve as useful tools to improve the quality of healthcare by facilitating the translation of evidence into practice [58]. Therefore, great efforts have been put in place by multiple scientific bodies and societies to develop best practice recommendations and propose pain care pathways.…”
Section: Inhomogeneous Pain Care Deliverymentioning
confidence: 99%
“…It has been suggested that clinical care pathways could serve as useful tools to improve the quality of healthcare by facilitating the translation of evidence into practice [58]. Therefore, great efforts have been put in place by multiple scientific bodies and societies to develop best practice recommendations and propose pain care pathways.…”
Section: Inhomogeneous Pain Care Deliverymentioning
confidence: 99%
“…Our analyses suggest that the location of potential rotator cuff tears can be predicted by considering the radiographic indices from shoulder X‐rays. Thus, if the location of shoulder pain is accordant with the location of a potential rotator cuff tear, it is easier for the clinician to make an accurate diagnosis 13 . Furthermore, by knowing the location of a potential rotator cuff tear, daily shoulder activity or exercise should be considered so as to avoid excessive use of the susceptible tendon 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, if the location of shoulder pain is accordant with the location of a potential rotator cuff tear, it is easier for the clinician to make an accurate diagnosis. 13 Furthermore, by knowing the location of a potential rotator cuff tear, daily shoulder activity or exercise should be considered so as to avoid excessive use of the susceptible tendon. 28 When sub‐acromial block therapy is required, the location of the potential rotator cuff injury can be predicted from radiographic indices, thus allowing clinicians to guide the drug distribution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations